Effect of BaSnO3 Nanoparticle Inclusion on Critical Current Density of GdBa2Cu3O7- Thin Films - Nhan, Duong Thi Thanh; Duc, Tran Hai (VNU Journal of Science: Mathematics - Physics; Vol 29 No 3, 2013)
Abstract: Effect of BaSnO 3 (BSO) nanoparticle inclusion on the critical current density of GdBa 2 Cu 3 O 7-x (GdBCO) thin films was investigated. BSO nanoparticles were prepared on a thin GdBCO seed layer of < 50 nm thick by using pulsed laser deposition (PLD) technique. The GdBCO superconducting layers were deposited on top of the BSO nanoparticles to produce films with the entire thickness of approximately 250 nm [O1]  . The number of laser pulses was varied from 20 to 320 in order to obtain BSO nanoparticles with different sizes and densities. Magnetization data measured at 65 K showed that: at a small number of laser pulses, the slight enhancement in critical current density (J c ) up to 1.5 T was obtained. Further increasing the number of laser pulses, J c s were found to be consistently decreased. The increase in J c was attributed to the addition of BSO nanoparticles serving as artificial pinning centers (APCs) inside GdBCO films. The decreases in J c was probably caused by to the crystallinity degradation of the BSO-doped GdBCO films which was confirmed by the larger FHWM values. Keywords: GdBCO thin film, critical current density, BaSnO 3 , artificial pinning centers.   [O1]